2020
DOI: 10.1111/papr.12900
|View full text |Cite
|
Sign up to set email alerts
|

Convergent and Discriminant Validity of the Serbian Version of the Central Sensitization Inventory

Abstract: Objectives The goal of the present study was to explore additional evidence of validity of the Serbian version of the Central Sensitization Inventory (CSI), a patient‐reported outcome measure of symptoms that have been found to be associated with central sensitization (CS). The CSI has been found to be psychometrically sound, and has demonstrated evidence of convergent and discriminant validity in numerous published studies and in multiple languages. Methods CSI data were collected from 399 patients with chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 63 publications
4
9
1
Order By: Relevance
“…Compared to the localized pain group, the multisite group scored significantly higher on the CSI-FI. Associations have been found between CSI scores and similar symptom reporting in other previous studies [27,33,34]. The results of the present study provide further evidence of discriminant validity of the CSI.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Compared to the localized pain group, the multisite group scored significantly higher on the CSI-FI. Associations have been found between CSI scores and similar symptom reporting in other previous studies [27,33,34]. The results of the present study provide further evidence of discriminant validity of the CSI.…”
Section: Discussionsupporting
confidence: 89%
“…Published results from previous cultural adaptations and validations suggest that the CSI is a reliable, valid, and consistent measure [32]. Previous studies have shown good discriminative ability of the CSI to distinguish between chronic pain subjects and control subjects without pain [32][33][34]. Associations have been found between CSI scores and other validated patient-reported measures of CS-related symptoms, including depression symptoms, kinesiophobia, perceived disability, health-related quality of life, and sleep problems [26,27,30,33] Due to rationale linking chronic pain syndromes and fibromyalgia with postural control instability, it was hypothesized that there may be a potential relationship between higher CSI scores and postural control instability on a force plate.…”
Section: Introductionmentioning
confidence: 96%
“…Also, the HC group differed significantly from all pain groups except the RCP group, which was believed to most likely have lower levels of CS. These finding are supported by Knezevic et al [ 64 ], who found similar results in FMS, multiple pain sites, and localized pain subgroups.…”
Section: Discussionsupporting
confidence: 81%
“…The PCS correlated to a small degree with the CSI-GE. This was unexpected as we believed that the concept of catastrophizing is an amplifying factor for CS, and previous CSI studies have reported higher correlations with the PCS [ 60 , 64 ]. Correlations with pain sensitivity and intensity were low.…”
Section: Discussionmentioning
confidence: 75%
“…We used the ODI in the present study because it is one of the few available disability questionnaires available in the Serbian language. However, though it has been used in previous studies that included non-spinal pain patients population [ 7 , 18 , 49 , 50 , 51 ], the ODI was designed for patients with low back pain [ 22 , 23 ]. Less than half of our study subjects reported low back pain.…”
Section: Discussionmentioning
confidence: 99%